New Quality of the Accounting Chamber of Ukraine: Development Strategy - V. Nevidomyi; K. Kanonishena-Kovalenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The international approaches to strategic planning in supreme audit institutions and current experience of European countries in developing such strategies are explored. The challenges and problems of external audit in Ukraine are defined in terms of the results of functional assessment and performance indicators of the Accounting Chamber. The development strategy structure, mission, vision, values and strategic goals of the Accounting Chamber are developed.